2021
DOI: 10.29245/2578-2959/2021/2.1235
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Mental Illness Stigma Reduction Interventions Among African Americans in The United States

Abstract: Among African Americans, the chronicity and severity of mental illness correlates with worse health outcomes and widens health disparities. Stigma related to mental illness compounds mental health disparities by creating barriers to help-seeking behavior. We examine the current tools designed to reduce mental illness stigma and promote improved mental health outcomes among African Americans. The authors reviewed the current evidence in the literature for such stigma reduction interventions. The review team dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Given that Black Americans experience several types of mental health stressors more than other racial and ethnic groups, this finding seems paradoxical. However, research has revealed that Black/African Americans are particularly susceptible to the prevalence and impacts of stigma related to mental illness, which frequently discourages them from getting care for their mental health (Rivera et al, 2021). While the study showed that Black/African Americans were less likely to experience mental health issues, we think this is due to the stigma associated with mental illness, thus, underreporting of experiences of such events.…”
Section: Discussionmentioning
confidence: 99%
“…Given that Black Americans experience several types of mental health stressors more than other racial and ethnic groups, this finding seems paradoxical. However, research has revealed that Black/African Americans are particularly susceptible to the prevalence and impacts of stigma related to mental illness, which frequently discourages them from getting care for their mental health (Rivera et al, 2021). While the study showed that Black/African Americans were less likely to experience mental health issues, we think this is due to the stigma associated with mental illness, thus, underreporting of experiences of such events.…”
Section: Discussionmentioning
confidence: 99%
“…Black and African-descended people of faith are a population that remains underrepresented in the design, development, and evaluation of both digital mental health and digital anti-stigma tools (Rivera et al, 2021). This work centers this priority population.…”
Section: Contributionsmentioning
confidence: 99%
“…prioritizing religious communities with a high prevalence of mental health stigma should address cultural factors specific to Black and African Americans, such as the racialization of mental illness and dimensions of religious involvement (Rivera et al, 2021). In addition, church leadership should be approached directly to partner with researchers when developing mental health and care-seeking interventions (Berkley-Patton et al, 2021).…”
Section: Considerations When Designing For Intersectional Identitiesmentioning
confidence: 99%
See 2 more Smart Citations